Seed Stability During Storage: Raffinose content and seed glassy state - Bernal-Lugo, I.
It has been proposed that sucrose and raffinose play a role in the storability of maize seeds. The levels of these sugars in the embryos and the glassy state were compared in maize seeds of contrasting storage stability to determine the relationship between sugar composition, glassy state and the storability of the seed. Sucrose was the predominant sugar but its content was not correlated with good storage. The content of raffinose as a mass fraction of total sugars and the magnitude of the glassy state showed positive correlations with storage stability. It is suggested that in maize seeds dry storage stability is a reflection not of the total soluble sugars, but of the mixture of sucrose with raffinose. Apparently raffinose amplifies the magnitude of the glass signal and this in turn is associated with enhanced storability.
Keywords: GLASS STATE; MAIZE; RAFFINOSE; SEED AGEING; STORABILITY; SUCROSE; SUGARS; ZEA MAYS L